Cannabinoids for treating neurogenic lower urinary tract dysfunction in patients with multiple sclerosis: a systematic review and meta‐analysis. (23rd February 2017) - Abo Youssef, Nadim; Schneider, Marc P.; Mordasini, Livio; Ineichen, Benjamin V.; Bachmann, Lucas M.; Chartier‐Kastler, Emmanuel; Panicker, Jalesh N.; Kessler, Thomas M.
Abstract : Objectives: To review systematically all the available evidence on efficacy and safety of cannabinoids for treating neurogenic lower urinary tract dysfunction (NLUTD) in patients with multiple sclerosis (MS). Patients and Methods: The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. Studies were identified by electronic search of the Cochrane register, Embase, Medline, Scopus (last search on 11 November 2016). Results: After screening 8 469 articles, we included two randomized controlled trials and one open‐label study, in which a total of 426 patients were enrolled. Cannabinoids relevantly decreased the number of incontinence episodes in all three studies. Pooling data showed the mean difference in incontinence episodes per 24 h to be −0.35 (95% confidence interval −0.46 to −0.24). Mild adverse events were frequent (38–100%), but only two patients (0.7%) reported a serious adverse event. Conclusions: Preliminary data imply that cannabinoids might be an effective and safe treatment option for NLUTD in patients with MS; however, the evidence base is poor and more high‐quality, well‐designed and adequately powered and sampled studies are urgently needed to reach definitive conclusions.